An ethical modernity? : Hegel's concept of ethical life today - Chotaš, Jiří, 1964-; Matějčková, Tereza, 1984- (Critical studies in German idealism, 2020)
"Modernity has neither a beginning nor an end. To be precise, we do not know when the period started and when (or if) it ended. Are we modern? Were we ever modern? And is "post- modernity" only a variation of modernity? These questions remain open. Just as the phenomenon of modernity is elusive, so is its definition. Yet, elusiveness never prevents thinkers from offering definitions. On the contrary, the very elusiveness is what incites these creative attempts. One of the most famous definitions of modernity does not originate with a philosopher but a poet. Baudelaire says that "modernity is the transient, the fleeting, the contingent; it is one half of art, the other being the eternal and the immovable" (Baudelaire 1972, 403). This understanding of modernity captures more than its fleetingness; it shows that anything with the tag "modern" has a built- in dimension of transience and finitude, so to speak. Taking inspiration from Baudelaire, we might arrive at a minimal- and by no means unproblematic- definition of modernity: Modern is that which is other than tradition, that which even opposes tradition"--